Hypocretin Receptor 1 Knockdown in the Ventral Tegmental Area Attenuates Mesolimbic Dopamine Signaling and Reduces Motivation for Cocaine - Bernstein, David L. (Addict Biol, 2017)
The hypocretin receptor 1 (HCRTr1) is a critical participant in the regulation of motivated behavior. Previous observations demonstrate that acute pharmacological blockade of HCRTr1 disrupts dopamine (DA) signaling and the motivation for cocaine when delivered systemically or directly into the ventral tegmental area (VTA). To further examine the involvement of HCRTr1 in regulating reward and reinforcement processing, we employed an adeno-associated virus to express a short-hairpin RNA designed to knock down HCRTr1. We injected virus into the VTA and examined the effects of HCRTr1 knockdown on cocaine self-administration and DA signaling in the nucleus accumbens (NAc) core. We determined that the viral approach was effective at reducing HCRTr1 expression without affecting the expression of HCRT receptor 2 or DA-related mRNAs. We next examined the effects of HCRTr1 knockdown on cocaine self-administration, observing delayed acquisition under a fixed-ratio schedule and reduced motivation for cocaine under a progressive ratio schedule. These effects did not appear to be associated with alterations in sleep/wake activity. Using fast scan cyclic voltammetry, we then examined whether HCRTr1 knockdown alters DA signaling dynamics in the NAc core. We observed reduced DA release and slower uptake rate as well as attenuated cocaine-induced DA uptake inhibition in rats with knock down of HCRTr1. These observations indicate that HCRTr1 within the VTA influence the motivation for cocaine, likely via alterations in DA signaling in the NAc.